2015
DOI: 10.1007/s00204-015-1633-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage response in cisplatin-induced nephrotoxicity

Abstract: Cisplatin and its derivatives are widely used chemotherapeutic drugs for cancer treatment. However, they have debilitating side-effects in normal tissues and induce ototoxicity, neurotoxicity, and nephrotoxicity. In kidneys, cisplatin preferentially accumulates in renal tubular cells causing tubular cell injury and death, resulting in acute kidney injury (AKI). Recent studies have suggested that DNA damage and the associated DNA damage response (DDR) is an important pathogenic mechanism of AKI following cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 86 publications
1
97
0
2
Order By: Relevance
“…Cisplatin is commonly used by gynecologists to kill tumor cells by inducing DNA damage, promoting cell cycle arrest and increasing the rate of apoptosis (6,7). Previous studies have reported the following mechanisms underlying chemotherapy resistance: Certain tumor cells exhibit enhanced DNA repair functions and a weakened apoptotic process, with the transformation to epithelial stroma facilitating the secretion of matrix protein enzymes, including matrix metalloproteinase (MMP)-2 and MMP-9, which enable these tumor cells to break through the basement membrane, metastasize and invade.…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin is commonly used by gynecologists to kill tumor cells by inducing DNA damage, promoting cell cycle arrest and increasing the rate of apoptosis (6,7). Previous studies have reported the following mechanisms underlying chemotherapy resistance: Certain tumor cells exhibit enhanced DNA repair functions and a weakened apoptotic process, with the transformation to epithelial stroma facilitating the secretion of matrix protein enzymes, including matrix metalloproteinase (MMP)-2 and MMP-9, which enable these tumor cells to break through the basement membrane, metastasize and invade.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the main cause of AKI includes ischemia/reperfusion injury, nephrotoxic damage, and sepsis (Basile et al, 2012; Togel and Westenfelder, 2014; Yang et al, 2016). Using various models of cisplatin-induced nephrotoxic AKI, we and others have delineated a rapid DDR in kidney cells and tissues(Zhu et al, 2015). Moreover, recent studies have begun to unveil DDR and its pathogenic role in renal ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Nephrotoxicity could be observed in as many as 38% of patients after the treatment with cisplatin . It would affect the cycles of chemotherapy, and then diminishing the antitumour effect . The initiation and progression of kidney injury by cisplatin were multifactorial, including biotransformation, adduct formation, oxidative stress, inflammation and changes in cell cycle .…”
Section: Introductionmentioning
confidence: 99%